Influence of Organizational Justice and Career Success to The Organizational Commitment - Nining Kunwantari, Marcham Darokah (Universitas Ahmad Dahlan, 2012)
This research aims to observe the organizational justice and career success as predictors of organizational commitment are made on the Civil Service. The members measure in Organizational Commitment Scale, Organizational Justice Scale and Career Success Scale. The 96 respondents are civil servants working at the health centre in Kulon Progo District Health Office. The data obtained was processed by Structural Equation Model (SEM). Based on the hypothesis, it can be concluded that organizational commitment can be explained by significant with p < 0.05 by organizational justice and career success, in the equation : Organizational Commitment = (0.451 Organizational Justice) + (0.483 Career Success). Influence contribution of Organizational Justice is 20.34 % and Career Success is 23.17 %. It gives consequences that organizational justice, career success and organizational commitment have be managed positively.